Pengembangan Modul Pembelajaran Kalkulus 1 Berbasis Problem Based Learning Di STMIK Duta Bangsa - Farida, Anisatul; Indah, Ratna Puspita (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
The purpose of this research is to develop module Calculus 1 based on the problem based learning that valid, practical, and effective in Calculus 1 at Information Engineering of STMIK Duta Bangsa. This research is development research using 4D model. The steps are defined, design, develop, and disseminate. The define steps are syllabus and textbook analysis, review of the literature, and interview about lesson and college student about learning in the classroom. The design step is the design of workbook. The developing steps are consists of validation, praktikalitas, and effectiveness. After designed, the workbook will be validated by the validator. At the praktikalitas step, workbook was tried out to students semester 1 Â of Information Engineering in STMIK Duta Bangsa. This event will be observed by an observer. The effectiveness of workbook observed at the same time with praktikalitas steps. The effect that observed were the activities and student learning outcomes. The technique of collecting data was done by validation sheet, observation sheet, field notes, and an interview. The data were analyzed using the descriptive set. The dissemination step was spread of the product. The outer of this research is a prototype, model, module of Calculus 1 and national journal publication. The result showed that the module of Calculus 1 was having validity very valid by content and construct. According to observation and interviews, note showed that module Calculus 1 was already practical and easy to used by students. The module of Calculus 1 is effective according to the study and observation activity students. This research was indicated that by using modules can improving activity and learning outcomes students.Keywords: module, problem-based learning, Kalkulus 1